Microwave combustion synthesis, magneto-optical and electrochemical properties of NiMoO4 nanoparticles for supercapacitor application. Issue 12 (15th August 2018) - Seevakan, K.; Manikandan, A.; Devendran, P.; Shameem, A.; Alagesan, T.
Abstract: Nickel molybdate (NiMoO4 ) nanoparticles (NPs) were synthesized by a simplistic one-pot microwave combustion method using urea as the fuel. The produced NPs have been examined by powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) analysis, scanning electron microscope (SEM), energy dispersive X-ray (EDX), high-resolution transmission electron microscopy (HR-TEM) analysis. Further, optical and electronic properties were determined by UV-Visible and Photoluminescence (PL) analysis, respectively. The magnetic performance of the NiMoO4 NPs was investigated by vibrating sample magnetometer (VSM) and the surface chemical composition was identified by X-ray photoelectron spectroscopy (XPS). The electrochemical activities of the NiMoO4 NPs were studied by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge/discharge (GCD) analysis. From the results, the CV curves indicated the occurrence of redox couples and besides with the EIS data (Nyquist plot), confirmed the supercapacitor nature of the synthesized NiMoO4 . The prepared NiMoO4 exhibits a high specific capacitance and rateability. This electrode grants a high specific capacitance of 450 F g −1 at 2 mA cm −2 and the well permanency with a cycling proficiency of 94% after 1000 cycles. These results clearly showed that the synthesized NiMoO4 NPs have potential application for the forthcoming flexible and lightweight energy storage.